The dimensions and implications of the public's reactions to the January 6, 2021, invasion of the U.S. Capitol - Jacobson, Gary C. 1944- (Cambridge University Press, 2024)
The January 6, 2021 invasion of the US Capitol building by a mob trying to block certification of Biden's victory attacked a bedrock principle of American democracy, the peaceful transfer of power following an election. This Element reviews how the pubic evaluated the invaders, their actions, Donald Trump's responsibility, and the House investigations as they evolved after January 6. It then analyzes these reactions in the broader context of contemporary American politics and considers the consequences of January 6 for the 2022 election, the Republican coalition, polarization, Trump's indictments, electoral politics in 2024, and the future health of American democracy
Title from publisher's bibliographic system (viewed on 29 Mar 2024)
Keywords: Capitol Riot, Washington, D.C., 2021; Riots -- Washington (D.C.) -- History -- 21st century; Domestic terrorism -- United States -- History -- 21st century; United States -- Politics and government -- 2017-2021